Synthesis, characterisation and antimicrobial activity of fluorobenzoylthioureas bearing a- and b-alanine - Mohamed, Nor Azanita; Ngah, Nurziana; Darnis, Deny Susanti (2014)
A series of fluorobenzoylthioreas bearing a- and b- alanine with different position of fluoro atom substitution have been successfully synthesised and characterised using CHNS micro elemental analysis and spectroscopic method including FTIR, UV-Vis and 1H and 13C NMR. Microelemental analysis data of the compounds were in agreement with the calculated values. The FTIR spectra showed the presence of important bands of the compounds and 1H and 13C exhibited expected chemical shift. Antibacterial and anti fungal activities have been evaluated by zone of inhibition, MIC and MBC/MFC studies against B.cereus, S.epidermidis, E. coli, P.aeruginosa, C. Albicans and T. metagrophytes. Most of the compounds showed moderate antibacterial activity against B.cereus and S.epidermidis and moderate to excellent anti fungal activity against T.metagrophytes. The antimicrobial activities of the compounds were related to the different position of fluoro atom substitution and a-and b-alanine presence in the compounds